Understanding Perceptions of Victimization: a Critical Analysis of Gay and Bisexual Male Grindr Users Negotiations of Safety and Risk - Colliver, Ben (The British journal of criminology, 2024)
The victimization of gay and bisexual men has gained significant academic and social attention, with that focus extending to the role of digital victimization. Grindr has dominated the market for online dating apps targeting gay, bisexual, trans and queer people. Drawing on qualitative data collected from men who use Grindr, this paper addresses a gap in criminological literature by exploring the way that men that have sex with men negotiate perceptions of safety when engaging in real-world meetings that have been facilitated by Grindr. It is argued throughout this paper that risk-reduction strategies adopted by interviewees only reduce the perception of risk, rather than the actual risk of experiencing violent victimization. As such, it is claimed exploring digital integration offers a more nuanced reading of the intertwined and fraught relations of risk and safety within digital and physical spaces.